MORRIS WATER MAZE – A BENCH MARK TEST FOR LEARNING AND MEMORY DISORDERS IN ANIMAL MODELS: A REVIEW - VENKATARAMAIAH, CH.; SWATHI, G.; RAJENDRA, W. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The morris water maze (MWM) was developed by morris as a device to investigate spatial learning and memory in laboratory rats. MWM has become one of the most frequently used laboratory tools in behavioral neuroscience. The MWM task has been often used in the validation of rodent models for neurocognitive disorders (e.g., Parkinson, Alzheimer, Epilepsy, and Schizophrenia), and the evaluation of possible neurocognitive treatments. It is also being used to assess the properties of established potential antipsychotics in animal models of Schizophrenia. The MWM task requires rats to find a hidden platform in a large, circular pool of water that is colored opaque with powdered non-fat milk (or) non-toxic tempera paint where they must swim to the hidden platform. Because they are in the opaque water, the animals cannot see the platform and cannot rely on scent to find the escape route. Instead, they must rely on extra-maze cues. The behavior of rat can be evaluated by analyzing the different parameters such as escape latency, swim speed, and path length, and probe trail. The purpose of this review is to briefly describe procedural aspects, interpretational difficulties of data and advantages of MWM. This paradigm has become a benchmark test for learning and memory difficulties in animal models and preclinical research in general.